Gut Microbiota and Their Role in Health and Metabolic Disease of Dairy Cow - Xu, Qingbiao; Qiao, Qinqin; Gao, Ya; Hou, Jinxiu; Hu, Mingyang; Du, Yufeng; Zhao, Ke; Li, Xiang (Frontiers in Nutrition, 2021)
Ruminants are mostly herbivorous animals that employ rumen fermentation for the digestion of feed materials, including dairy cows. Ruminants consume plant fibre as their regular diet, but lack the machinery for their digestion. For this reason, ruminants maintain a symbiotic relation with microorganisms that are capable of producing enzymes to degrade plant polymers. Various species of microflora including bacteria, protozoa, fungi, archaea, and bacteriophages are hosted at distinct concentrations for accomplishing complete digestion. The ingested feed is digested at a defined stratum. The polysaccharic plant fibrils are degraded by cellulolytic bacteria, and the substrate formed is acted upon by other bacteria. This sequential degradative mechanism forms the base of complete digestion as well as harvesting energy from the ingested feed. The composition of microbiota readily gets tuned to the changes in the feed habits of the dairy cow. The overall energy production as well as digestion is decided by the intactness of the resident communal flora. Disturbances in the homogeneity gastrointestinal microflora has severe effects on the digestive system and various other organs. This disharmony in communal relationship also causes various metabolic disorders. The dominance of methanogens sometimes lead to bloating, and high sugar feed culminates in ruminal acidosis. Likewise, disruptive microfloral constitution also ignites reticuloperitonitis, ulcers, diarrhoea, etc. The role of symbiotic microflora in the occurrence and progress of a few important metabolic diseases are discussed in this review. Future studies in multiomics provides platform to determine the physiological and phenotypical upgradation of dairy cow for milk production.